An efficient emerging network and secured hopping scheme employed over the unsecured public channels - Aamir Shahzad; Kaiwen Zhang; René Landry; Neal Xiong; Young-Gab Kim (International Journal of Distributed Sensor Networks, 2020)
With the emergence of new smart technologies, including the Internet of Things, wireless media are playing an important role to connect numerous devices to fulfill the requirements of newly developed communication systems. The massive connectivity, therefore, made the wireless spectrum too crowded and gave several challenges to resisting against potential wireless jammers. Note that, the two main challenges that have always been a part of any communication system, especially in the case of wireless communication, are information security and information jamming. Carefully considering the given challenges, this study uses a new advanced anti-jamming approach, a modulation technique based on the frequency-hopping spread spectrum, which has notably high resistance accounted against various potential jammers. The objective of this study is two-fold. First, the physical channel properties are considered, and the random bits are transmitted, employing a cryptographic secured hoping-spread pattern, having a set of carrier frequencies, known at both sides of the transmission. Second, the hashing code is computed only for the key, and transmitted along the original hopset, but with distinct frequencies set. The deployed practical anti-jamming approach, therefore, computed a high efficiency to examine the information secrecy well and primarily the connection availability even in the presence of the jammers. Moreover, this study considered and modeled a communication system and evaluated the proposed system’s performance, applying the theories of Shannon’s entropy and Wyner’s entropy (i.e. Wyner’s wiretap channel), to anticipate the system’s perfect secrecy, even in the worst case when jammer has unlimited computational capabilities.